Grain-oriented electrical steel sheet
By controlling the amount of Co and Ti, an orientation electromagnetic steel plate with low assembly coefficient was prepared, which solved the problem of increasing iron loss of the transformer core, and achieved the effect of reducing iron loss and assembly coefficient and improving magnetic characteristics.
Patent Information
- Application Number
- CN202380063616.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-09
- Filing Date
- 2023-09-04
- Publication Date
- 2025-04-15
AI Technical Summary
In the prior art, there is a deviation between the iron loss value of the transformer core and the iron loss value of the blank material, resulting in an increase in the iron loss of the transformer core and unable to exert sufficient performance.
By controlling the amount of Co in the base steel plate and the amount of Ti in the steel plate in the state of the base film with forsterite as the main component, an orientation electromagnetic steel plate with low assembly coefficient was prepared.
It realizes the reduction of the iron loss and assembly coefficient of the transformer core, improves the magnetic characteristics, and enhances the performance of the transformer.
Smart Images

Figure CN119836484A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a grain-oriented electromagnetic steel sheet suitable for an iron core material of a transformer. Background Art
[0002] Grain-oriented electromagnetic steel sheet is a soft magnetic material used as the core material of transformers. <001> This texture is formed by making the {110} so-called Goss orientation during the purification annealing process in the manufacturing process of the grain-oriented electrical steel sheet. <001> The preferential growth of oriented grains is a phenomenon called secondary recrystallization.
[0003] As for the formation method, a general technique is to use a precipitate called an inhibitor to cause secondary recrystallization of grains having a Goss orientation during purification annealing. For example, the method using AlN and MnS described in Patent Document 1 and the method using MnS and MnSe described in Patent Document 2 have been put into practical use in industry.
[0004] The method of using these inhibitors is an effective method for stably developing secondary recrystallized grains. In order to finely disperse the inhibitors in steel, it is necessary to heat the slab at a high temperature of 1300°C or higher to dissolve the inhibitor components all at once.
[0005] On the other hand, Patent Document 3 and the like disclose a technique for developing Goss-oriented grains by secondary recrystallization in a billet that does not contain inhibitor components. This technique is to exclude impurities such as inhibitor components as much as possible, so that the grain boundary orientation difference angle dependence of the grain boundary energy of the grain boundary during primary recrystallization is revealed, and the grains with Goss orientation are secondary recrystallized even without the use of inhibitors. This effect is called texture suppression effect. In this method, since it is not necessary to finely disperse the inhibitor in the steel, it is also not necessary to heat the slab at a high temperature, which was previously required. This method has great advantages in terms of cost and maintenance.
[0006] Grain-oriented electromagnetic steel sheets are mainly used as the core of transformers, and they are required to have excellent magnetization characteristics, especially low iron loss. Therefore, it is important to make the secondary recrystallized grains in the steel sheet highly consistent with the Goss orientation and to reduce impurities in the product sheet. In addition, a technology has been developed that introduces unevenness into the surface of the steel sheet by physical methods and subdivides the width of the magnetic domain to reduce iron loss, namely, magnetic domain refinement technology. For example, Patent Document 4 proposes a technology that introduces a high dislocation density area into the surface of the steel sheet by irradiating the final product sheet with a laser, thereby reducing the width of the magnetic domain and reducing the iron loss of the steel sheet. In addition, Patent Document 5 proposes a technology for controlling the width of the magnetic domain by irradiating an electron beam.
[0007] The above-mentioned alignment of the orientation after secondary recrystallization with the Goss orientation and the reduction of impurities in the product sheet lead to a reduction in hysteresis loss. In contrast, if the magnetic domain refinement technology is applied, the eddy current loss is mainly reduced.
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent Document 1: Japanese Patent Publication No. 40-15644
[0011] Patent Document 2: Japanese Patent Publication No. 51-13469
[0012] Patent Document 3: Japanese Patent Application Laid-Open No. 2000-129356
[0013] Patent Document 4: Japanese Patent Publication No. 57-2252
[0014] Patent Document 5: Japanese Patent Publication No. 6-72266 Summary of the invention
[0015] As mentioned above, the grain-oriented electromagnetic steel sheet is mainly used as the iron core of the transformer. Generally speaking, there is a deviation between the iron loss value of the transformer core and the iron loss value of the grain-oriented electromagnetic steel sheet as the blank, and the iron loss of the transformer core is large. The iron loss ratio of the two (the value obtained by dividing the iron loss of the transformer core by the iron loss value of the blank) is called the assembly factor (building factor). That is, even if the iron loss of the blank is good, if the assembly factor is high, the iron loss of the transformer core increases, resulting in the problem of not being able to exert sufficient performance. In the era of carbon neutrality, what should be reduced is the iron loss of the transformer as the final product. No matter how low the iron loss of the blank is, it is meaningless if the assembly factor is high. Since the assembly factor not only affects the design of the transformer, but also affects the characteristics of the blank, it is necessary to reduce the iron loss of the blank and the assembly factor.
[0016] That is, an object of the present invention is to provide a grain-oriented electrical steel sheet having magnetic properties capable of sufficiently reducing the assembly factor.
[0017] As a result of intensive studies, the present inventors have found that by controlling the amount of Co in a base steel sheet having a base film mainly composed of forsterite and the amount of Ti in a grain-oriented electrical steel sheet having the base film formed thereon within certain ranges, a grain-oriented electrical steel sheet with a low assembly factor can be manufactured.
[0018] The following describes experiments that successfully implemented the present invention.
[0019] <Experiment 1>
[0020] In order to mainly change the Co content, a steel slab containing, by mass%, C: 0.050-0.081%, Si: 3.15-3.31%, Mn: 0.07-0.10%, Al: 0.020-0.025%, N: 0.0069-0.0085%, S: 0.0011-0.0031%, Sb: 0.025-0.036%, Co: 0-0.123%, and Ti: 0.0080-0.0090%, with the remainder being Fe and inevitable impurities, was produced by continuous casting, and the slab was heated at 1400°C for 20 minutes by soaking, and then hot rolled to a thickness of 2.4 mm. Then, hot rolled sheet annealing was performed at 1000°C for 30 seconds in a N2 atmosphere. Next, cold rolling was performed to a plate thickness of 1.5 mm, and intermediate annealing was further performed at 1000°C for 100 seconds in a 25% H2-75% N2 atmosphere. Then, the plate thickness was cold rolled to 0.23 mm, and decarburization annealing was performed at 850°C for 150 seconds in a wet atmosphere of 50% H2-50% N2 and a dew point of 50°C. Next, an annealing separator mainly composed of MgO was applied to the surface of the base steel plate after decarburization annealing, and a purification annealing was performed at 1200°C for 10 hours. At this time, the heating rate to 1200°C was 20°C / h, and further during the heating process, the N2 atmosphere was used from room temperature to 700°C, the atmosphere obtained by changing the mixing ratio of N2 and H2 from 700°C to 1100°C was used, and the H2 atmosphere was used from 1100°C to 1200°C. In addition, the H2 atmosphere was used during holding, and the Ar atmosphere was used during cooling. In this way, a sample was obtained in which a base film mainly composed of forsterite (hereinafter, sometimes referred to as forsterite film) was formed on the surface of the base steel plate.
[0021] The iron loss W of the obtained samples was measured according to the method specified in JIS C2550-1. 17 / 50 (iron loss when excited to 1.7T at 50Hz) and W 19 / 50 (iron loss when excited to 1.9T at 50Hz), and hysteresis loss Wh 17 (Hysteresis loss when exciting to 1.7T) and Wh 19 (Hysteresis loss when excitation is performed to 1.9T).
[0022] In order to measure the Co content in the base steel plate, a part of the obtained sample was immersed in a 10% hydrochloric acid aqueous solution at 80° C. for 180 seconds to remove the forsterite film and the Co content was measured according to the method specified in JIS G1222.
[0023] Next, a three-phase three-leg model transformer with a 500 mm square shape and a 100 mm plate width for each leg and each yoke was made from the obtained sample, and the iron loss WT of the model transformer was measured.17 / 50 (Transformer iron loss when excited to 1.7T at 50Hz). The number of stacked samples was set to 50, and two were stacked alternately. The assembly factor F17 of the model transformer was used as the model transformer iron loss WT 17 / 50 Divide by the iron loss W of the sample 17 / 50 The value obtained (WT 17 / 50 / W 17 / 50 The relationship between the assembly coefficient F17 and the amount of Co in the base steel plate is shown in Figure 1 .
[0024] According to the Figure 1 As shown in the results, no obvious correlation was observed between the assembly coefficient F17 and the amount of Co. However, Figure 1 It can be seen that the fitting coefficient F17 is divided into good values below 1.25 and high values above 1.30.
[0025] Therefore, we studied whether the difference can be explained by the relationship between the iron loss and hysteresis loss of the samples. As a result, we found that the hysteresis loss Wh when excited at 1.7 T is 17 and iron loss W 17 / 50 Wh 17 / W 17 / 50 Set R17 to Wh when exciting at 1.9T. 19 and iron loss W 19 / 50 Wh 19 / W 19 / 50 When R19 is used, the system is divided into a group A satisfying the relationship of 0.30≤R17≤R19 and a group B other than the group A. Figure 2 Only extract Figure 1 The data in Group A are plotted again.
[0026] According to the Figure 2 The results shown show that the steel sheets belonging to group A, that is, having the relationship of 0.30≤R17≤R19, exhibited a good assembly coefficient of 1.25 or less when the Co content was in the range of 0.005 to 0.050%.
[0027] Experiment 2
[0028] A steel slab containing C: 0.037%, Si: 3.05%, Mn: 0.18%, Al: 0.009%, N: 0.0036%, Se: 0.007%, Sn: 0.062% and Co: 0.0080% by mass, and the remainder being Fe and inevitable impurities, is produced by continuous casting, and the slab is heated at 1300°C for 30 minutes for soaking, and then hot rolled to a thickness of 2.2 mm. Then, hot rolled sheet annealing is performed at 1100°C for 30 seconds in a N2 atmosphere. Next, cold rolling is performed to a sheet thickness of 0.23 mm, and decarburization annealing is further performed at 840°C for 120 seconds in a wet atmosphere of 40% H2-60% N2 and a dew point of 40°C. Next, the surface of the base steel plate after decarburization annealing was coated with an annealing separator obtained by mixing TiO2 with MgO in various amounts in the range of 0 to 15 parts by mass, and a purification annealing was performed at 1220°C for 5 hours. At this time, the heating rate to 1220°C was 15°C / h. In addition, during the heating process, the atmosphere was N2 from room temperature to 700°C, the atmosphere was N2 with various mixing ratios of N2 and H2 from 700°C to 1100°C, and the atmosphere was H2 from 1100°C to 1220°C. In addition, the atmosphere was H2 during holding and Ar during cooling. Thus, a sample was obtained in which a base film (hereinafter sometimes referred to as forsterite film) with forsterite as the main component was formed on the surface of the base steel plate.
[0029] The iron loss W of the samples thus obtained was measured in the same manner as in Experiment 1 according to the method specified in JIS C2550-1. 17 / 50 and W 19 / 50 And hysteresis loss Wh 17 and Wh 19 .
[0030] In addition, the amount of Ti in the steel sheet having the forsterite film was measured according to the method specified in JIS G1223.
[0031] Furthermore, in order to measure the Co content in the base steel plate, a portion of the obtained sample was immersed in a 10% hydrochloric acid aqueous solution at 80°C for 180 seconds to remove the forsterite film, and then subjected to the measurement of the Co content according to the method specified in JIS G1222. As a result, the Co content was 0.0080%, which was the same as that of the steel slab.
[0032] Furthermore, similarly to Experiment 1, the hysteresis loss Wh when the magnetization is performed at 1.7 T is calculated. 17 and iron loss W 17 / 50 Wh 17 / W 17 / 50 Set R17 to Wh when exciting at 1.9T. 19 and iron loss W 19 / 50 Wh19 / W 19 / 50 Assuming R19, the steel sheet is divided into Group A with a relationship of 0.30≤R17≤R19 and Group B with the other relationship. The relationship between the amount of Ti in the steel sheet having a forsterite film and whether it belongs to Group A or Group B is shown in FIG. Figure 3 .
[0033] According to the Figure 3 The results shown show that when the amount of Ti in the steel sheet having the forsterite film is 0.0039% to 0.0200%, there is a tendency to belong to the A group.
[0034] In addition, similar to Experiment 1, a three-phase three-leg model transformer with a 500 mm square shape and a 100 mm plate width for each leg and each yoke was made, and the iron loss WT of the model transformer was measured. 17 / 50 (Transformer iron loss when excited to 1.7T at 50Hz). And, the assembly factor F17 of the model transformer is taken as the model transformer iron loss WT 17 / 50 Divide by the iron loss W of the sample 17 / 50 The value obtained (WT 17 / 50 / W 17 / 50 The relationship between the assembly coefficient F17 and the amount of Ti in the steel sheet having a forsterite film is shown in Figure 4 shown.
[0035] By Figure 4 The results shown show that when the amount of Ti in the steel sheet with the forsterite film is less than 0.0050%, the assembly coefficient F17 is high even if it belongs to group A. In summary, when the amount of Ti in the steel sheet with the forsterite film is 0.0050-0.0200%, the assembly coefficient is low and good. In short, this means that it is good to have a certain amount of Ti in the forsterite film.
[0036] As described above, the mechanism by which the Co content in the base steel sheet and the Ti content in the steel sheet having a base film mainly composed of forsterite improve the assembly factor of the model transformer is not yet clear, but the inventors consider the following.
[0037] That is, since the yoke and leg of the transformer have a certain width, the magnetic circuit has different distances on the inside and outside, like a track in an athletic competition. Therefore, when excited, there is a tendency for the magnetic flux to shift to the inside where the magnetic circuit is shorter. Even if the steel plate is excited to 1.7T as a whole, the magnetic flux density on the inside exceeds that of the steel plate. From this, it can be inferred that the more favorable the high magnetic field characteristics are, the better the transformer characteristics such as the assembly coefficient. If Co is dissolved in iron, the saturation magnetic flux density of iron is expected to increase and the high magnetic field characteristics are improved, so it is believed that the assembly coefficient is optimized. However, in Experiments 1 and 2, there are two cases where the assembly coefficient is not good even if Co is added.
[0038] The first is the hysteresis loss Wh when excited at 1.7T. 17 and iron loss W 17 / 50 Wh 17 / W 17 / 50 That is, R17 and the hysteresis loss Wh when excited at 1.9T 19 and iron loss W 19 / 50 Wh 19 / W 19 / 50 That is, R19 does not satisfy the relationship of 0.30≤R17≤R19. After a detailed investigation, it was found that R17 is lower than 0.30 in most cases. Hysteresis loss is highly correlated with B8. If B8 is the same, it is believed that there is no significant change, so it is believed that the above is a case where eddy current loss is extremely large. In the transformer, it can be considered that even if the excitation is performed with a sine wave, the high-frequency components overlap and the waveform is distorted, so it is believed that the eddy current loss with high frequency dependence increases. Therefore, it is believed that if the eddy current loss ratio is high, the assembly factor increases.
[0039] The second is a case where the amount of Ti in the steel sheet having a forsterite film is less than 0.0050 mass % or greater than 0.0200 mass %. Although it is an inference, it is believed that the film properties will be improved by the presence of a certain amount of Ti in the forsterite film. For example, if the film tension is increased, the magnetic domain is refined, and there is a possibility of reducing eddy current loss. In this case, contrary to the above-mentioned R17 and R19, the eddy current loss ratio decreases, so it is believed that the assembly coefficient can be reduced.
[0040] That is, Japanese Patent Publication No. 2021-509149 discloses a technology for producing a grain-oriented electrical steel sheet containing Co. However, the document mentions a technology for improving the magnetic properties of the electrical steel sheet itself, which is completely different from the present invention that uses a technology for containing Ti in a forsterite film to reduce the assembly coefficient.
[0041] The present invention is based on the above findings. That is, the main configuration of the present invention is as follows.
[0042] 1. A grain-oriented electrical steel sheet comprising a base steel sheet and a base film,
[0043] The base steel plate contains Si: 1.50-8.00 mass %, Mn: 0.02-1.00 mass % and Co: 0.005-0.050 mass %,
[0044] The base film is formed on the surface of the base steel plate and is mainly composed of forsterite;
[0045] The Ti content of the base steel plate and the base film as a whole is 0.0050 to 0.0200 mass %,
[0046] Hysteresis loss Wh when exciting at 1.7T 17 and iron loss W 17 / 50 Wh 17 / W 17 / 50 Set R17 to Wh when exciting at 1.9T. 19 and iron loss W 19 / 50 Wh 19 / W 19 / 50 When R19 is used, the following formula (1) is satisfied.
[0047] 0.30≤R17≤R19···(1)
[0048] 2. The grain-oriented electrical steel sheet according to item 1 above, wherein the amount of Ti in the base steel sheet is 0.0030 mass % or less.
[0049] 3. The grain-oriented electrical steel sheet according to item 1 or 2 above, wherein the base film has an insulating film on the surface thereof.
[0050] 4. The grain-oriented electrical steel sheet according to any one of 1 to 3 above, wherein the base steel sheet further contains one or more selected from the group consisting of Sn: 0.500 mass% or less, Cr: 0.500 mass% or less, Cu: 0.50 mass% or less, Ni: 0.50 mass% or less, Bi: 0.500 mass% or less, P: 0.500 mass% or less, Sb: 0.500 mass% or less, Mo: 0.500 mass% or less, B: 25.0 mass ppm or less, Nb: 0.020 mass% or less, V: 0.020 mass% or less, As: 0.0200 mass% or less, Zn: 0.020 mass% or less, Pb: 0.0100 mass% or less, W: 0.0100 mass% or less, Ga: 0.0050 mass% or less, and Ge: 0.0050 mass% or less.
[0051] According to the present invention, it is possible to provide a grain-oriented electrical steel sheet having magnetic properties and capable of sufficiently reducing the assembly factor. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 This is a graph showing the relationship between the Co content of the base steel plate and the assembly coefficient F17 according to Experiment 1.
[0053] Figure 2 This is a diagram showing the relationship between the Co content of the base steel plate and the assembly coefficient F17 according to Experiment 1 (only Group A is extracted).
[0054] Figure 3 This is a diagram showing the relationship between the amount of Ti in the steel sheet having the forsterite film according to Experiment 2 and whether the steel sheet belongs to the A group or the B group.
[0055] Figure 4 This is a graph showing the relationship between the Ti content of the steel sheet having a forsterite film according to Example 2 and the assembly coefficient F17. DETAILED DESCRIPTION
[0056] Next, the reasons for limiting the constituent elements of the present invention are explained. First, the amounts of each element (component composition) in the parent steel sheet of the grain-oriented electrical steel sheet of the present invention are explained. It should be noted that, unless otherwise specified, the "%" and "ppm" symbols related to the component composition represent "mass %" and "mass ppm", respectively.
[0057] Si: 1.50~8.00%
[0058] Si is an element required to increase the resistivity of steel and improve iron loss. In addition, Si is also an element required to form the forsterite film in the steel plate of the present invention. However, if the Si content is less than 1.50%, there is no effect, and if it is greater than 8.00%, the workability of the steel deteriorates and it is difficult to roll. Therefore, the Si content is limited to 1.50 to 8.00%. The Si content is preferably 2.50% or more, and preferably 4.50% or less.
[0059] Mn: 0.02~1.00%
[0060] Mn is an element necessary for improving hot workability. However, if the Mn content is less than 0.02%, there is no effect, and if it is greater than 1.00%, the magnetic flux density of the product sheet decreases. Therefore, the Mn content is set to 0.02-1.00%. The Mn content is preferably 0.04% or more, and preferably 0.20% or less.
[0061] Co: 0.005~0.050%
[0062] For the above reasons, Co needs to be contained in an amount within a range of 0.005% to 0.050%. The Co amount is preferably 0.006% or more, more preferably 0.008% or more. In addition, the Co amount is preferably 0.020% or less, more preferably 0.015% or less.
[0063] The parent steel sheet of the grain-oriented electrical steel sheet of the present invention may contain C (e.g., 0.020 to 0.100%), Al (e.g., 0.002 to 0.040%), and N (e.g., 0.002 to 0.015%) in addition to the above-mentioned basic components (Si, Mn, and Co). In addition, the parent steel sheet may arbitrarily contain S (e.g., 0.020% or less) and / or Se (e.g., 0.040% or less). In addition, the parent steel sheet of the grain-oriented electrical steel sheet of the present invention may contain the following components (elements) as appropriate, in addition to the above-mentioned components.
[0064] Specifically, in order to improve the magnetic properties, the base steel plate may be selected from Sn: (greater than 0%) 0.500% or less, Cr: (greater than 0%) 0.500% or less, Cu: (greater than 0%) 0.50% or less, Ni: (greater than 0%) 0.50% or less, Bi: (greater than 0%) 0.500% or less, P: (greater than 0%) 0.500% or less, Sb: (greater than 0%) 0.500% or less, Mo: (greater than 0%) 0.500% or less, B: (greater than 0%) 0.500% or less, )25.0ppm or less, Nb: (greater than 0%) 0.020% or less, V: (greater than 0%) 0.020% or less, As: (greater than 0%) 0.0200% or less, Zn: (greater than 0%) 0.020% or less, Pb: (greater than 0%) 0.0100% or less, W: (greater than 0%) 0.0100% or less, Ga: (greater than 0%) 0.0050% or less and Ge: (greater than 0%) 0.0050% or less, or a combination of two or more thereof.
[0065] That is, in order to further improve the magnetic properties, the above-mentioned elements can be contained in the base steel plate within the above-mentioned upper limit amount range. If the addition amount (content) of each element exceeds the above-mentioned upper limit value, the development of secondary recrystallized grains may be inhibited, and the magnetic properties may be deteriorated. It should be noted that the lower limit value of each element does not need to be particularly limited, and is preferably in the following range.
[0066] Sn: 0.005% or more, Cr: 0.005% or more, Cu: 0.01% or more, Ni: 0.01% or more, Bi: 0.005% or more, P: 0.005% or more, Sb: 0.005% or more, Mo: 0.005% or more, B: 0.1ppm or more, Nb: 0.001% or more, V: 0.001% or more, As: 0.0010% or more, Zn: 0.001% or more, Pb: 0.0001% or more, W: 0.0010% or more, Ga: 0.0001% or more, and Ge: 0.0001% or more
[0067] In the base steel plate, the remainder other than the above-mentioned components (elements) is Fe and inevitable impurities.
[0068] The above-mentioned composition is the composition of the base steel plate, that is, the base film mainly composed of forsterite is not taken into account. In the present invention, due to the above reasons, the amount of Ti in the steel plate having a base film mainly composed of forsterite, that is, the amount of Ti in the base steel plate and the base film as a whole is limited to 0.0050-0.0200%. The amount of Ti in the base steel plate and the base film as a whole is preferably 0.0060% or more, and preferably 0.0150% or less.
[0069] In addition, regarding the base film, the "main component" refers to the component with the largest mass among the components constituting the base film.
[0070] Here, when the amount of Ti in the steel plate in the state of having a base film is limited to 0.0050-0.0200%, the amount of Ti in the parent steel plate is preferably 0.0030% or less. This is because if the amount of Ti in the parent steel plate is 0.0030% or less, it is possible to suppress the significant deterioration of iron loss caused by the precipitates of Ti produced in the steel. On the other hand, the amount of Ti in the steel plate in the state of having a base film is 0.0050% or more. This is because, as mentioned above, by the presence of a certain amount of Ti in the forsterite film, the film properties can be improved and the eddy current loss can be improved, but if the amount of Ti is less than 0.0050%, it is estimated that the effect is insufficient.
[0071] In addition, in the present invention, as described above, it is necessary to limit the range of parameters calculated from the hysteresis loss and iron loss of the product steel sheet. That is, it is necessary to make the hysteresis loss Wh when exciting at 1.7 T 17 and iron loss W 17 / 50 Ratio R17(=Wh 17 / W 17 / 50 ) and the hysteresis loss Wh when excited at 1.9T 19 and iron loss W 19 / 50 Ratio R19(=Wh 19 / W19 / 50 ) satisfies the relationship of 0.30≤R17≤R19. These values can be measured according to the method specified in JIS C2550-1. It should be noted that in order to match the iron loss at 50 Hz, the hysteresis loss can be the value obtained by multiplying the energy loss of the iron core caused by rotating the hysteresis loop once by the excitation frequency 50.
[0072] Next, the method for manufacturing the directional electromagnetic steel sheet of the present invention is described. The manufacturing method can utilize a general method for manufacturing electromagnetic steel sheets. For example, molten steel adjusted with a specified composition can be used to manufacture slabs using a conventional ingot casting method or a continuous casting method, or a thin cast sheet with a thickness of less than 100 mm can be manufactured using a direct casting method. The molten steel can be manufactured by a blast furnace method or an electric furnace method. Since the various components that may be contained in the above-mentioned base steel plate are difficult to add in the middle process, it is preferably added in the molten steel stage. The slab can be heated and hot rolled using a conventional method, or hot rolled immediately after casting without heating. In a component system with a small amount of inhibitor components, high-temperature annealing is not required for dissolving the inhibitors, so setting the heating temperature to a low temperature of less than 1300°C is effective for the purpose of reducing costs. The temperature during heating is preferably less than 1250°C.
[0073] Next, hot rolled sheet annealing is performed as needed. The temperature of hot rolled sheet annealing is preferably about 950-1150°C. If it is above 950°C, the residue of the non-recrystallized part can be fully suppressed. In addition, if it is below 1150°C, the excessive coarsening of the grain size after annealing can be suppressed, and the subsequent primary recrystallization texture can be further optimized. The temperature of hot rolled sheet annealing is preferably above 1000°C, and preferably below 1100°C.
[0074] The steel sheet after hot rolling or hot-rolled sheet annealing is cold-rolled once or twice or more with intermediate annealing to become a cold-rolled sheet with the final sheet thickness. The annealing temperature of the intermediate annealing is preferably in the range of 900 to 1200°C. If it is above 900°C, it is possible to well suppress the recrystallized grains after the intermediate annealing from becoming too fine, and in addition, it is possible to well suppress the reduction in the magnetic properties of the product sheet accompanying the reduction of the Goss nuclei in the primary recrystallization structure. On the other hand, if it is below 1200°C, as with the hot-rolled sheet annealing, it is possible to suppress the excessive coarsening of the grains and make the primary recrystallization structure of the regular grains better.
[0075] Then, the cold rolled sheet having the final sheet thickness is subjected to primary recrystallization annealing which also serves as decarburization annealing. In the case of decarburization annealing, the annealing temperature in the primary recrystallization annealing is preferably in the range of 800 to 900° C. from the viewpoint of rapidly advancing the decarburization reaction, and the atmosphere is preferably a humid atmosphere.
[0076] Then, by applying an annealing separator mainly composed of MgO and then performing purification annealing, a secondary recrystallized structure can be developed to form a forsterite film. Here, mainly composed of MgO means that MgO is contained in an amount of 75 mass % or more.
[0077] Furthermore, by adding a Ti compound to the annealing separator and introducing a N2 atmosphere during the purification annealing described later, Ti can be effectively made present in the forsterite film. However, other methods can also be used to make Ti present in the forsterite film.
[0078] Next, secondary recrystallization annealing (purification annealing) is performed. In order to express secondary recrystallization, the purification annealing is preferably performed at a temperature of 800°C or above, and from the viewpoint of purification, it is preferably heated to a holding temperature of 1100°C or above. The holding temperature is more preferably above 1180°C. The longer the holding time here, the more the purification proceeds, but the shape deteriorates due to high temperature creep, so 3 hours to 15 hours is preferred. After the purification annealing, in order to remove the attached annealing separator, water washing, brushing or pickling is preferably performed. In addition, from the viewpoint of obtaining the desired iron loss characteristics, in the heating process of the purification annealing, it is preferred that the atmosphere is N2 until the first temperature (for example, a temperature selected from the range of 600 to 800°C), a mixed atmosphere of N2 and H2 from the first intermediate temperature to the second intermediate temperature (for example, a temperature selected from the range of 1050 to 1150°C), and an H2 atmosphere from the second intermediate temperature to the holding temperature.
[0079] Then, flattening annealing is performed to correct the shape, which is effective in reducing iron loss. It should be noted that when stacked steel plates are used, it is effective to apply an insulating film to the surface of the steel plate before or after flattening annealing in order to improve iron loss. As the insulating film, a film that can apply tension to the steel plate is preferred in order to reduce iron loss. A method of forming a film by depositing an inorganic substance on the surface of a steel plate by a tension film coating method via an adhesive, a physical vapor deposition method, or a chemical vapor deposition method is preferred because the film has excellent adhesion and has a significant iron loss reduction effect.
[0080] Example
[0081] Hereinafter, the present invention will be described in detail with reference to Examples, but the present invention is not limited to these.
[0082] (Example 1)
[0083] Billet A···Contains C: 0.070%, Si: 3.55%, Mn: 0.07%, Al: 0.0080%, N: 0.0050%, Co: 0.012%, Mo: 0.026%, Ti: 0.025%, and the remainder is Fe and unavoidable impurities
[0084] Billet B···Contains C: 0.072%, Si: 3.51%, Mn: 0.07%, Al: 0.0080%, N: 0.0047%, Co: 0.011%, Mo: 0.025%, Ti: 0.0025%, and the remainder is Fe and unavoidable impurities
[0085] Billet C···Contains C: 0.072%, Si: 3.49%, Mn: 0.07%, Al: 0.0090%, N: 0.0051%, Co: 0.002%, Mo: 0.025%, Ti: 0.024%, and the remainder is Fe and unavoidable impurities
[0086] Billet D···Contains C: 0.068%, Si: 3.48%, Mn: 0.07%, Al: 0.0090%, N: 0.0050%, Co: 0.008%, Mo: 0.022%, Ti: 0.0010%, and the remainder is Fe and unavoidable impurities
[0087] The above-mentioned steel billets A to D were respectively manufactured by continuous casting, and the slabs were heated by soaking at 1200°C for 40 minutes, and then hot rolled to a thickness of 2.2 mm. Then, hot rolled sheet annealing was performed at 1000°C for 60 seconds in N2 atmosphere. Next, cold rolling was performed to a sheet thickness of 0.23 mm, and further, decarburization annealing was performed at 850°C for 90 seconds in a wet atmosphere of 60% H2-40% N2 and a dew point of 60°C.
[0088] Next, an annealing separator mainly composed of MgO (MgO: 97 mass%) was applied to the surface of the base steel plate after decarburization annealing, and a purification annealing was performed by holding at 1100°C for 25 hours and then at 1200°C for 10 hours. In this heating process, the N2 atmosphere was used from room temperature to 700°C, the atmosphere obtained by changing the mixing ratio of N2 and H2 from 700°C to 1100°C was used, and the H2 atmosphere was used from 1100°C (holding start) to 1200°C (holding end). Furthermore, the Ar atmosphere was used during cooling.
[0089] The Ti content (Ti content in the entirety of the base steel plate and the base film) of the thus obtained sample, i.e., the steel plate having a base film mainly composed of forsterite, was measured according to the method specified in JIS G1223. The results are collectively shown in Table 1.
[0090] An insulating film mainly composed of magnesium phosphate and silicon dioxide was applied on the base film of the steel sheet. The iron loss W of the obtained sample was measured according to the method specified in JIS C2550-1. 17 / 50 (iron loss when excited to 1.7T at 50Hz) and W 19 / 50(iron loss when excited to 1.9T at 50Hz), and hysteresis loss Wh 17 (Hysteresis loss when exciting to 1.7T) and Wh 19 (Hysteresis loss when excitation is performed to 1.9T). 17 / W 17 / 50 (ie R17) and Wh 19 / W 19 / 50 (i.e. R19) are marked in Table 1.
[0091] Furthermore, in order to measure the amount of Co and Ti in the base steel plate, a portion of the obtained sample was immersed in a 10% hydrochloric acid aqueous solution at 80°C for 180 seconds to remove the base film, and then subjected to measurement according to the method specified in JIS G1222 and JIS G1223. The measurement results are also shown in Table 1.
[0092] Next, a three-phase three-leg model transformer with a 500 mm square shape and a 100 mm plate width for each leg and each yoke was made from the sample with the insulating film formed thereon, and the iron loss WT of the model transformer was measured. 17 / 50 (Transformer iron loss when excited to 1.7T at 50Hz). The number of stacked samples was set to 50, and two were stacked alternately. The assembly factor F17 of the model transformer was used as the model transformer iron loss WT 17 / 50 Divide by the iron loss W of the sample 17 / 50 The value obtained (WT 17 / 50 / W 17 / 50 The results are recorded in Table 1.
[0093] [Table 1]
[0094]
[0095] As can be seen from Table 1, in the samples (grain-oriented electrical steel sheets) according to the present invention, good iron loss characteristics (assembly coefficient) can be obtained.
[0096] (Example 2)
[0097] A steel slab containing the components shown in Table 2 and the remainder being Fe and inevitable impurities is manufactured by continuous casting, and the slab is heated by soaking at 1410°C for 20 minutes, and then hot rolled to a thickness of 2.4 mm. Then, hot rolled sheet annealing is performed at 1100°C for 20 seconds in N2 atmosphere. Next, cold rolling is performed to a sheet thickness of 1.5 mm, and further intermediate annealing is performed at 900°C for 100 seconds in 25% H2-75% N2 atmosphere. Then, cold rolling is performed to a sheet thickness of 0.23 mm, and decarburization annealing is performed at 825°C for 150 seconds in a wet atmosphere of 40% H2-60% N2 with a dew point of 45°C.
[0098]
[0099] Next, an annealing separator mainly composed of MgO (MgO: 88 mass%) was applied to the surface of the base steel plate after decarburization annealing. 5 mass parts of superhydrated TiO2 was added to the annealing separator relative to MgO. The superhydrated TiO2 was obtained by filtering TiO2 powder after being put into warm water at 50°C and stirred for 24 hours.
[0100] In addition, purification annealing was performed at 1200°C for 10 hours. At this time, the heating rate to 1200°C was 15°C / h, and further, during the heating process, the N2 atmosphere was used from room temperature to 700°C, the atmosphere was variously changed in the mixing ratio of N2 and H2 from 700°C to 1100°C, and the H2 atmosphere was used from 1100°C to 1200°C. In addition, the H2 atmosphere was used during the holding period, and the Ar atmosphere was used during the cooling period.
[0101] The Ti content (Ti content in the entirety of the base steel plate and the base film) of the thus obtained sample, i.e., the steel plate having a base film mainly composed of forsterite, was measured according to the method specified in JIS G1223. The measurement results are collectively shown in Table 3.
[0102] An insulating film mainly composed of magnesium phosphate and silicon dioxide was applied on the base film of the steel sheet. The iron loss W of the obtained sample was measured according to the method specified in JIS C2550-1. 17 / 50 (iron loss when excited to 1.7T at 50Hz) and W 19 / 50 (iron loss when excited to 1.9T at 50Hz), and hysteresis loss Wh 17 (Hysteresis loss when exciting to 1.7T) and Wh 19 (Hysteresis loss when excitation is performed to 1.9T). 17 / W 17 / 50 (ie R17) and Wh 19 / W 19 / 50 (i.e. R19) are marked together in Table 3.
[0103] Furthermore, in order to measure the amount of Co and Ti in the base steel plate, a part of the obtained sample was immersed in a 10% hydrochloric acid aqueous solution at 80°C for 180 seconds to remove the base film, and then subjected to measurement according to the method specified in JIS G1222 and JIS G1223. The measurement results are also shown in Table 3.
[0104] Next, a three-phase three-leg model transformer with a 500 mm square shape and a 100 mm plate width for each leg and each yoke was made from the sample with the insulating film formed thereon, and the iron loss WT of the model transformer was measured. 17 / 50 (Transformer iron loss when excited to 1.7T at 50Hz). The number of stacked samples was set to 50, and two were stacked alternately. The assembly factor F17 of the model transformer was used as the model transformer iron loss WT 17 / 50 Divide by the iron loss W of the sample 17 / 50 The value obtained (WT 17 / 50 / W 17 / 50 The results are recorded in Table 3.
[0105]
[0106] As can be seen from Table 3, in the samples (grain-oriented electrical steel sheets) according to the present invention, good iron loss characteristics (assembly coefficient) can be obtained.
Claims
1. A grain-oriented electrical steel sheet comprising a base steel sheet and a base film, The base steel plate contains Si: 1.50-8.00 mass %, Mn: 0.02-1.00 mass % and Co: 0.005-0.050 mass %, The base film is formed on the surface of the base steel plate and is mainly composed of forsterite; The Ti content of the base steel plate and the base film as a whole is 0.0050 to 0.0200 mass %, Hysteresis loss Wh when exciting at 1.7T 17 and iron loss W 17 / 50 Wh 17 / W 17 / 50 Set R17 to Wh when exciting at 1.9T. 19 and iron loss W 19 / 50 Wh 19 / W 19 / 50 When R19 is set, the following formula (1) is satisfied: 0.30≤R17≤R19···(1).
2. The grain-oriented electrical steel sheet according to claim 1, wherein: The amount of Ti in the base steel plate is 0.0030 mass % or less.
3. The grain-oriented electrical steel sheet according to claim 1 or 2, wherein: The base film has an insulating film on its surface.
4. The grain-oriented electrical steel sheet according to any one of claims 1 to 3, wherein The base steel plate further contains one or more selected from Sn: 0.500 mass% or less, Cr: 0.500 mass% or less, Cu: 0.50 mass% or less, Ni: 0.50 mass% or less, Bi: 0.500 mass% or less, P: 0.500 mass% or less, Sb: 0.500 mass% or less, Mo: 0.500 mass% or less, B: 25.0 mass ppm or less, Nb: 0.020 mass% or less, V: 0.020 mass% or less, As: 0.0200 mass% or less, Zn: 0.020 mass% or less, Pb: 0.0100 mass% or less, W: 0.0100 mass% or less, Ga: 0.0050 mass% or less, and Ge: 0.0050 mass% or less.
Citation Information
Patent Citations
JP1976013469B2
Improving method for iron loss characteristic of directional electrical steel sheet
JP1982002252B2
Manufacturing method of ultra-low iron loss unidirectional silicon steel sheet
JP1994072266B2
Production of grain oriented silicon steel sheet
JP2000129356A
Grain-oriented electrical steel sheet and its manufacturing method
JP2021509149A